Reengineering university education : an economic and qualitative assessment. - Lim, Ern Lih. (2008)
The global economy and increased competition have brought about the need for a change and improvement of the current university education system so as to produce graduates who are capable of handling the new challenges. This report starts off by recognizing the fee differences between a private and public university. A survey on the satisfaction of undergraduates towards the current education system is conducted in both NUS and NTU.